Evaluation of Some Mechanical Properties of Dental Co-Cr alloys Fabricated by Casting and Selective Laser Melting (Journal of Hama University, 2021)
The aim of this paper is to study the mechanical properties (hardness and tensile strength) of Co-Cr alloys fabricated by casting technique (CS) and selective laser melting technique (SLM). Four sets of metallic samples made from dental Co-Cr alloys were made (Each one = 10 specimen) by using casting and selective laser melting techniques . Hardness and tensile strength were studied for each technique, Results revealed that there were statistically significant differences between the groups made by the two methods (0. 05 > P) . The average hardness of specimens manufactured by SLM technology was higher than specimens were manufactured by CS technology , and the average of tensile strength of specimens manufactured by SLM technology was higher than specimens made by CS method . It was concluded that manufacturing technique used had an effect on the mechanical properties of the dental Co-Cr alloy .